PENGARUH CELAH FIN, SUDUT KEMIRINGAN FIN DAN CELAH SUDU TERHADAP KINERJA TURBIN ANGIN SAVONIUS TYPE V - Kastiawan, I Made; Gofur, Abdul; Catur Pamungkas, Angga; Budianto, Aries (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2017)
This article is the result of research on wind turbine savonius type V. In thisresearch designed 4 blade type V which has angle 110 ÌŠ. This windmill analyzes the effect offin gaps, fin angle and blade slits. This windmill is designed by analyzing the lowest wind byutilizing the wind speed of passing vehicles on the road. The results of the study showed that5 mm fin breaks, a1 blade slits, b1 (5mm, 2.5mm) and fin angle of 30 ÌŠ can improve goodperformance. These results are evidenced by a maximum rotation speed of 96.7 Rpm and amaximum force of 1.4 N.